PEMANFAATAN TUMBUHAN OBAT UNTUK MENGATASI GANGGUAN SISTEM PENCERNAAN OLEH SUKU DAYAK IBAN: STUDI KASUS DI KABUPATEN KAPUAS HULU KALIMANTAN BARAT - yusro, fathul; Mariani, Yeni; Wardenaar, Evy (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
The study aims to analyze the utilization of medicinal plants of Dayak Iban in Kapuas Hulu Regency, West Kalimantan, especially its use to treat digestive system disorders. The methodology used were purposive sampling with semi-structured interviews. 100% of households of Tekalong and Bejabang sub-villages (Lanjak Besar village) and Tematu 1 and Tematu 3 sub-villages (Sepandan village) were selected as respondents. Data were analyzed through use value (UV), informant consensus factor (ICF) and fidelity level (FL) to obtain the utilization pattern of medicinal plants. A total of 21 species of medicinal plants are used by 60% of respondents to treat digestive system disorders. Plants with high UV are Allium cepa followed by Musa acuminata and Psidium guajava (0,53; 0,5, and 0,44, respectively). Plants with high ICF are used to treat gastric, thrush, laxative, defecation, and colds (1; 1; 1; 0.98; and 0.98, respectively). The plants with high FL (100) are Syzgium poliantum (diarrhea), Lansium domesticum (flatulence), Vitex pubescens (gastric), and Citrus amblycarpa (thrush), Durio zibethinus (sore tongue), Musa acuminata and Carica papaya (defecation), Piper nigrum, Cassia alata and Imperata cylindrica (stomachache), Alium cepa (cold), Mimosa pudica (toothache), Zingiber casumounar and Eleutherine bulbosa (hemorrhoids), Zingiber officinale and Kaempferia galanga (appetite enhancer), and Allium tuberosum (laxative). Zingiberaceae are highly plants family used by the respondents, and most of the plants are herbs (43%). Leaves and oral administration are mostly used by Dayak Iban to treat digestive system disorders.